Jenang Karomah Marketing Strategy and Its Impact on Women's Purchase Intention - Yulia Friyanni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Jenang Karomah is a business brand that has been established for 24 years to experience the dynamics of sales ups and downs. It is estimated that there is a link between variables of marketing strategy and service quality, especially for women buyers. This variable encourages researchers to research more about marketing strategies which include product, price, place, promotion. This study aims to analyze the marketing strategy of Jenang Karomah in Kudus and their impact on women's buying interest. The research method used in this study is a qualitative method, namely observation and interviews as data collection techniques. The results found four strategies developed by Jenang Karomah. First, the product strategy; packing with a good color, shape and brand, although still found packaging that is less tidy or defective. Second, place strategy; Jenang Karomah is located near the Kudus City Center where the majority of the community are also jenang sellers which results in competition to attract women buyers. Third, pricing strategies; Jenang Karomah fluctuates prices, especially during the moments of the big day before Lebaran or celebration which results in women's buying interest becoming very selective. Fourth, promotion strategies; Jenang Karomah has done offline promotions, but lacks promotion based on internet technology, namely social media such as YouTube, Instagram, Facebook, and Twitter which are widely used by young women as potential buyers. Four strategies developed by Jenang Karomah have influenced women's buying interest in Kudus City. The research method used in this study is qualitative with a descriptive analytical approach.